2020
DOI: 10.1088/1361-6528/ab7de7
|View full text |Cite
|
Sign up to set email alerts
|

Self-powered, all-solution processed, trilayer heterojunction perovskite-based photodetectors

Abstract: Heterostructures composed of nano-/micro-junctions, combining the excellent photon harvesting properties of nano-systems and the ultrafast carrier transfer of micro-systems, have a promising role in high-performance photodetectors. In this paper, a highly-sensitive trilayer self-powered perovskite-based photodetector ITO/ZnO (70 nm)/CdS (150 nm)/CsPbBr3 (200 nm)/Au, in which the CdS nanorods (NRs) layer is sandwiched between a ZnO/CsPbBr3 interface to reduce the interfacial charge carriers’ recombination and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 37 publications
(36 reference statements)
1
13
1
Order By: Relevance
“…The responsivity and detectivity of self‐powered photodetectors obtained in the present study were compared with reported perovskite‐based sandwiched‐type devices, as shown in Figure . [ 8,19,42,45–52 ] The responsivity and detectivity reported in the present study are superior compared with prior relevant studies. The superior performance obtained from self‐powered photodetectors via CVD deposited perovskite films might be attributed to the high intrinsic quality of the perovskite films (high quality compact films and with no pinholes).…”
Section: Resultscontrasting
confidence: 62%
“…The responsivity and detectivity of self‐powered photodetectors obtained in the present study were compared with reported perovskite‐based sandwiched‐type devices, as shown in Figure . [ 8,19,42,45–52 ] The responsivity and detectivity reported in the present study are superior compared with prior relevant studies. The superior performance obtained from self‐powered photodetectors via CVD deposited perovskite films might be attributed to the high intrinsic quality of the perovskite films (high quality compact films and with no pinholes).…”
Section: Resultscontrasting
confidence: 62%
“…In addition, the interaction between the atoms within the crystal was strengthened, as estimated by the XPS analysis. Layered structures have been used to improve the stability of nanomaterials, subsequently involving the intercalation of nanomaterials such as MoS 2 , ZnO, and graphene between the layers. ,, In this study, the charge-transfer layer made of MoS 2 nanoflakes was used for the fabrication of a photosensor.…”
Section: Resultsmentioning
confidence: 99%
“…To improve the sensitivity, charge-transfer layers such as ZnO, graphene, TiO 2 , and CdS have also been used in photosensors based on CsPbX 3 NCs. , These charge-transfer layers have been used to improve the efficiency of the separation of electron–hole pairs owing to their high electron mobility. These layers accelerate the charge carrier transport and enhance the sensitivity of the photosensors.…”
Section: Introductionmentioning
confidence: 99%
“…Under these conditions, the CsPbBr 3 was excited by a large number of electron–hole pairs, causing photogenerated electrons to flow into the ZnO NWs, thereby increasing conductivity and eliminating the depletion region with a corresponding increase in the current. As shown in Figure b, the extremely small scale of CsPbBr 3 (a few nanometers) produced strong quantum effects, resulting in the generation of far more electron–hole pairs than were generated in ZnO NWs. , Note that the main absorption band of the PQD film was in the green light region, such that the generation of the photocurrent greatly exceeded that of pure ZnO NWs.…”
Section: Resultsmentioning
confidence: 99%